Patofisiologi dan Faktor Predisposisi yang Berhubungan dengan Omphalocele - Angel D. Rarung; Harsali F. Lampus; Eko Prasetyo (Medical Scope Journal, 2023)
Abstract: Omphalocele is one of the most common congenital abnormalities of the abdominal wall. In various countries, the incidence of omphalocele ranges from 1-3.8 per 10,000 pregnancies. This study aimed to determine the pathophysiology and predisposing factors associated with omphalocele. This was a literature review study. Literatures were obtained through several databases: Pubmed, ClinicalKey, and Google Scholar. The results showed 22 articles that fulfilled the inclusion criteria. The pathophysiology of omphalocele was when the abdominal organs herniate for an extended period of time, in results failing the intra-abdominal organs from returning to their normal position. Predisposing factors associated with omphalocele were divided into two aspects namely maternal and neonatal. In conclusion, the pathophysiology of omphalocele is still the same from year to year with the existing theory that there has not been a shift or discoveries. In contrast, for predisposing factors, several studies have reported new aspects of maternal and neonates about factors related to omphalocele. Keywords: omphalocele; pathophysiology; predisposing factors   Abstrak: Omphalocele adalah salah satu kelainan kongenital dinding abdomen yang paling umum terjadi, Insiden omphalocele berkisar pada 1-3,8 per 10.000 kehamilan di berbagai negara. Penelitian ini bertujuan untuk mengetahui patofisiologi dan faktor predisposisi yang berhubungan dengan omphalocele. Jenis penelitian ialah suatu literature review. Literatur diperoleh melalui beberapa basis data yaitu Pubmed, ClinicalKey, dan Google Scholar. Hasil penelitian mendapatkan 22 artikel yang sesuai dengan kriteria inklusi. Patofisiologi omphalocele yaitu ketika terjadi herniasi fisiologis berkepanjangan dari organ abdomen sehingga terjadi kegagalan organ intraabdomen untuk kembali ke posisi normalnya. Faktor predisposisi yang berhubungan dengan omphalocele terbagi atas dua aspek yaitu maternal dan neonatus. Simpulan penelitian ini ialah patofisiologi dari omphalocele masih sama dari tahun ke tahun dengan teori yang ada dimana belum terjadi pergeseran atau penemuan baru sedangkan untuk faktor predisposisinya terdapat beberapa penelitian yang melaporkan hal baru terkait aspek maternal dan neonatus yang berhubungan dengan omphalocele. Kata kunci: omphalocele; patofisiologi; faktor predisposisi